Prototype Website Rov(Remotely Operated Vehicles) Using The Internet Of Things - Aknov H; Aprilinda Y (International Conference on Engineering and Technology Development (ICETD), 2017)
Increasingly knowledge is growing rapidly. One of these is evolving knowledge about robotic technology, Robotics in today has become an important part of human life. Robots are Eletromechanical equipment or bio-mechanical, or a combination of equipment that generates the autonomy movement and the movement based on movement ordered.Robot in some cases can replace the role of man, as seen on the robots are applied in various fields such as industry,health(health),defense(defense),agriculture(agriculture),research(research),ploy(game),vehicles(smartvehicle) and others.Smart vehicle that is being developed is a Remotely Operated Vehicle (ROV),ROV(RemotelyOperatedVehicles)is a tool that serves a kind of robot to search underwater sonar andcamera equipped. ROV has the ability to observe objects in the ocean and is controlled by remote control from directly above the water surface.ROV can provide convenience to the people to not have to go and dive marine observing various resources that exist in the oceans. by using this tool a person need only look at the data recorded by the ROV were put to sea in a monitor, and send all the data into a website via an internet connection which can later be accessed via computer or mobile device. To be able to upload data- research data from the vehicle via the internet have a problem because they have not had a personal website, on the background is the background of the manufacturing system for ROV website.